2013
DOI: 10.1038/sc.2013.135
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the global incidence of traumatic spinal cord injury

Abstract: Understanding the incidence of TSCI is important for health service planning and for the determination of injury prevention priorities. In the absence of high-quality epidemiological studies of TSCI in each country, the estimation of TSCI obtained through population modelling can be used to overcome known deficits in global spinal cord injury (SCI) data. The incidence of TSCI is context specific, and an alternative regression model demonstrated how TSCI incidence estimates could be improved with additional dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 27 publications
(22 reference statements)
0
65
0
2
Order By: Relevance
“…The estimated annual incidence reported in this study (more than 26 persons per million population) is relatively high as compared to the reported globally and in low income countries (23 and 25.5 persons per million population) respectively [5,12,18]. However there are other country and regional–specific studies that have reported higher annual incidences such as in Cape Town – South Africa and the United States which reports 75 and 54 persons per million population respectively [8,19].…”
Section: Discussionmentioning
confidence: 64%
“…The estimated annual incidence reported in this study (more than 26 persons per million population) is relatively high as compared to the reported globally and in low income countries (23 and 25.5 persons per million population) respectively [5,12,18]. However there are other country and regional–specific studies that have reported higher annual incidences such as in Cape Town – South Africa and the United States which reports 75 and 54 persons per million population respectively [8,19].…”
Section: Discussionmentioning
confidence: 64%
“…The absence of national reporting, illustrated by the 'Red Zone' areas in the global maps, makes it difficult to determine valid population denominators. Using the methods outlined by Fitzharris et al, 55 it could be possible to extrapolate data to appropriate regions and to adjust for variables, such as socio-economic development, which influence NTSCI. NTSCI data are currently inadequate for this approach.…”
Section: Box 1 Zones Of Information*mentioning
confidence: 99%
“…Fitzharris et al 1 have unquestionably done a wonderful job in the estimation of SCI worldwide; however, there are some points we would like to mention here. Fitzharris et al 1 have used the raw population data as a model in the estimation of SCI patients in each country. They have used data from 17 countries to run a statistical model of SCI incidence worldwide.…”
mentioning
confidence: 76%
“…We read the paper by Fitzharris et al 1 with great interest and care. Fitzharris et al 1 have unquestionably done a wonderful job in the estimation of SCI worldwide; however, there are some points we would like to mention here.…”
mentioning
confidence: 99%
See 1 more Smart Citation